PENGARUH BOARD STRUCTURE TERHADAP FINANCIAL PERFORMANCE MELALUI VOLUNTARY DISCLOSURE DAN EARNINGS MANAGEMENT - Amanda Kurniawans; Devie Devie Devie (Business Accounting Review, 2017)
The effect of board structure (board independence and board size) on financial performance had been studied in the past. However, there were only few studies about the impact of board structure on financial performance through voluntary disclosure and earnings management. The aim of this research was to examine the effect of board structure on financial performance through voluntary disclosure and earnings management.          This study was conducted on LQ45 firms between the period of 2011 to 2015 with total sample of 40 firms. The result showed that board independence had a significant positive impact on financial performance. It was also found that voluntary disclosure and earnings management were unable to mediate the effect of board on financial performance.